ACTIVITIES OF THE UKRAINIAN CANADIAN COMMITTEE DURING WORLD WAR II (1939 – 1945) - KRUKOVSKYI , Vitalii (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is a comprehensive analysis of the Ukrainian Canadian Committee participation (UCC) in the Canadian federal government’s campaign for war efforts aimed at moral and material support for the country’s armed forces and the Ukrainian servicemen present there in order to bring about victory over Nazi Germany in World War II, and its struggle with the Ukrainian Society for Aid to the Motherland (USAM) and the Assossiation of Canadian Ukrainians (ACU). The methodological basis of the study is the principles of objectivity, historicism, consistency, and problem-based approach. In the research the following methods have been used: analysis and synthesis, problem-chronological, comparative, to study the role of the UCC and ACU in Canada’s war efforts, as well as the method of internal criticism of sources. The scientific novelty consists in processing of a significant number of primary sources and scientific literature, which made it possible to analyze the forms and content of the UCC’s campaign in support of the Canadian federal government’s course on war efforts to defeat Nazi Germany in World War II and to compare the Ukrainian Canadian Committee and the Assossiation of Canadian Ukrainians in the context of the war and the Ukrainian issue. The Conclusions. The leadership of the Ukrainian Canadian Committee, together with its constituent and other public, youth, and cultural and educational organizations, from the moment of its founding in Winnipeg on November 6–7, 1940, conducted an agitation campaign among the youth of the Ukrainian diaspora of Canada by publishing declarations, communiqués, appeals in the press, announcing art evenings, performances, raffles and other events to collect donations for the needs of the Canadian Armed Forces, and rallied around itself all the “loyal elements” of the Ukrainian community in this country. The Ukrainian Canadian Committee supported the morale of 35,000–40,000 Ukrainian servicemen of the Canadian Armed Forces abroad, providing them with material and moral assistance. The contribution of Canadian Ukrainians and their leadership in the form of the Ukrainian Canadian Committee to the victory over Nazi Germany in World War II was highly appreciated by the Anglo-Canadian press, Canadian state and public figures, scientists, and all other friends of the country’s Ukrainian community and its researchers. The participation of the Ukrainian Canadian Committee in the war efforts of the residence country of the Ukrainian diaspora contributed to the deep socio-political integration of the community into civilized Canadian society, instilled in its representatives self-confidence as full citizens at a fateful time for Canada and the world. Having held its first Congress on June 22–24, 1943 in Winnipeg, the main national patriotic representative organization of Canadian Ukrainians, countering the Soviet and Sovietophile propaganda, was able to establish itself as an authoritative body representing and defending the interests of Canadian Ukrainians before the federal government and the Canadian public. Key words: the Ukrainian Canadian Committee, Assossiation of Canadian Ukrainians, Ukrainian Society for Aid to the Motherland, federal government of Canada, Canadian war effort, British Empire.